Cultures of Solitude Loneliness - Limitation - Liberation - Bergmann, Ina; Hippler, Stefan (Peter Lang International Academic Publishing Group, 2017)
This collection of essays comprises cultural analyses of practices of eremitism and reclusiveness in the USA, which are inseparably linked to the American ideals of individualism and freedom. Covering a time frame from the eighteenth to the twenty-first century, the essays study cultural products such as novels, poems, plays, songs, paintings, television shows, films, and social media, which represent the costs and benefits of deliberate withdrawal and involuntary isolation from society. Thus, this book offers valuable contributions to contemporary cultural discourses on privacy, surveillance, new technology, pathology, anti-consumerism, simplification, and environmentalism. Solitaries can be read as trailblazers for an alternative future or as symptoms of a pathological society.